Wage control and inflation in the Soviet bloc countries - Adam, Jan (London : Macmillan, 1979)
This book deals with wage control and inflation in the following five most important countries of the Soviet bloc - the USSR, Poland, the GDR, Czechoslovakia and Hungary.
A small part of the material in this study was previously published in various journals.
Includes index.
Bibliography: p. 232-237.
osc 8/5/18
Loans
Keywords: Wage-price policy; Inflation (Finance); Wages